Solution NMR structure of CHU_1110 from Cytophaga hutchinsonii, an AHSA1 protein potentially involved in metal ion stress response. Issue 1 (11th November 2018) - Liang, Chunjie; Zhu, Jiang; Ramelot, Theresa A.; Kennedy, Michael A.; Yue, Xiali; Li, Xuegang; Liu, Maili; He, Ting; Yang, Yunhuang
Abstract: We report the solution nuclear magnetic resonance (NMR) structure of CHU_1110 from Cytophaga hutchinsonii . CHU_1110 contains three α‐helices and one antiparallel β‐sheet, forming a large cavity in the center of the protein, which are consistent with the structural characteristics of AHSA1 protein family. This protein shows high structural similarities to the prokaryotic proteins RHE_CH02687 from Rhizobium etli and YndB from B acillus subtilis, which can bind with flavinoids. Unlike these two homologs, CHU_1110 shows no obvious interaction with flavonoids in NMR titration experiments. In addition, no direct interaction has been observed between CHU_1110 and ATP, although many homologous sequences of CHU_1110 have been annotated as ATPase. Combining the analysis of structural similarity of CHU_1110 and genomic context of its encoding gene, we speculate that CHU_1110 may be involved in the stress response of bacteria to heavy metal ions, even though its specific biological functions that need to be further investigated.